Salvage CD20-SD-CART therapy in aggressive B-cell lymphoma after CD19 CART treatment failure - Xue, Fei; Zheng, Peihao; Yang, Fan; Liu, Rui; Feng, Shaomei; Guo, Yuelu; Shi, Hui; Ma, Lixia; Deng, Biping; Xu, Teng; Zhang, Jiecheng; Zhou, Qi; et al. (Frontiers in Oncology, 2024)
Background and aims: Patients with relapsed/refractory aggressive B-cell lymphoma (r/r aBCL)who progressed after CD19-specific chimeric antigen receptor T-cell therapy (CD19CART) had a poor prognosis. Application of CAR T-cells targeting a second different antigen (CD20) expressed on the surface of B-cell lymphoma as subsequent anti-cancer salvage therapy (CD20-SD-CART) is also an option. This study aimed to evaluate the survival outcome of CD20-SD-CART as a salvage therapy for CD19 CART treatment failure. Methods: This retrospective cohort study enrolled patients with aBCL after the failure of CD19 CART treatment at Beijing Gobroad Boren Hospital from December 2019 to May 2022. Patients were subsequently treated with CD20CART therapy or non-CART therapy (polatuzumab or non-polatuzumab). Results: A total of 93 patients were included in the study, with 54 patients receiving CD20-SD-CART therapy. After a median follow-up of 18.54 months, the CD20-SD-CART group demonstrated significantly longer median progression-free survival (4.04 months vs. 2.27 months, p=0.0032) and median overall survival (8.15 months vs. 3.02 months, p<0.0001) compared to the non-CART group. The complete response rate in the CD20-SD-CART group (15/54, 27.8%) was also significantly higher than the non-CART group (3/38, 7.9%, p=0.03). Multivariate analysis further confirmed that CD20CART treatment was independently associated with improved overall survival (HR, 0.28; 95% CI, 0.16-0.51; p<0.0001) and progression-free survival (HR, 0.46; 95% CI, 0.27-0.8; p=0.005).Conclusion: CD20-SD-CART could serve as an effective therapeutic option for patients with relapsed or refractory aggressive B-cell lymphoma after CD19CART treatment failure.